2013
DOI: 10.1055/s-0033-1344234
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale multicenter study of long-term outcomes after endoscopic resection for submucosal invasive colorectal cancer

Abstract: Endoscopic resection alone is adequate for the management of patients with SM-CRC and low risk features. However, in those patients with SM-CRC and high risk features, surgery should be considered in addition to endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 19 publications
7
110
1
Order By: Relevance
“…Colorectal surgery is however associated with an overall mortality of 1–5% and morbidity of about 30%, especially in the elderly population 1–4. A recent study from Japan showed that endoscopic resection is adequate for T1 CRC with a low risk for lymph node metastasis (LNM), which concerns approximately 19–29% of all T1 CRCs 5 6. Additional surgical resection is required for high-risk T1 CRC 5…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal surgery is however associated with an overall mortality of 1–5% and morbidity of about 30%, especially in the elderly population 1–4. A recent study from Japan showed that endoscopic resection is adequate for T1 CRC with a low risk for lymph node metastasis (LNM), which concerns approximately 19–29% of all T1 CRCs 5 6. Additional surgical resection is required for high-risk T1 CRC 5…”
Section: Introductionmentioning
confidence: 99%
“…Careful lesion assessment before EMR or ESD is essen tial, primarily to avoid an attempt at endoscopic resection in a lesion containing deep submucosal invasion, which would be hazardous (increased risk of perforation) and would probably result in incomplete excision 7,39,40 . All lesions should be classified according to gross morpho logy using the internationally recognized Paris classifica tion 41 .…”
Section: Lesion Assessmentmentioning
confidence: 99%
“…Application of immunohistochemistry for D2-40 and desmin is informative to accurately detect vascular invasion and depth of submucosal invasion. Two large-scale retrospective multicenter cohort studies have shown that for patients with submucosal invasive CRC without the above risk factors, the 5-year overall survival rates were similar whether they were treated by endoscopic resection alone or underwent endoscopic resection with subsequent surgery [37,38]. …”
Section: Histological Assessmentmentioning
confidence: 99%